The Relationship of 2D:4D Finger Length Ratio with Biomotoric Characteristics and Sports Performance in Adolescent Basketball Players - Erkan Çetinkaya; Halil Tanır; Furkan Çelik (OVS LLC, 2024)
Background. The aim of this study is to determine the relationship of 2D:4D finger length ratio (also known as digit ratio) with biomotoric features and sports performance in adolescent basketball players. 24 male basketball players with a mean age of 14.83±0.71 years and a training age of 7.08±1.92 years participated in the study. Materials and methods. The participants' 2D and 4D finger lengths of both hands, height (cm), body weight (kg), some biomotoric characteristics and sports performances were determined by measurements. The German Heidelberger Basketball Test was conducted to evaluate the basketball-based sports performances of the participants. The SPSS 25.0 package program was performed in the statistical analysis of the obtained data. The Shapiro-Wilk test was used to determine whether or not the data showed a normal distribution. Parametric tests were preferred for statistical analysis as the data were found to have a normal distribution. Results. It was found that there was no statistically significant relationship between the 2D:4D finger length ratio, some motoric features and basketball-based sports performances of the participants (p>0.05). It was concluded that the ratio of 2D:4D finger lengths in adolescent basketball players did not have an effect on biomotoric features and basketball-based sports performance. When the correlation between 2D:4D finger length ratio and sports performance parameters was examined, no statistically significant relationship was observed (p>0.05). Conclusions. Although some studies show a significant negative correlation between performance tests and the 2D:4D ratio, it should be noted that the 2D:4D finger ratio is not the only determinant for sports performance.